2009
DOI: 10.1111/j.1365-3121.2008.00857.x
|View full text |Cite
|
Sign up to set email alerts
|

Neogene exhumation of the Marrakech High Atlas (Morocco) recorded by apatite fission‐track analysis

Abstract: Apatite fission‐track (AFT) data have been obtained along a traverse across the Marrakech High Atlas to constrain its tectono‐thermal evolution. AFT ages vary between 212 ± 15 Ma and 20 ± 4 Ma. An Early Miocene AFT age accompanied by long mean track length from the central part of the chain has been interpreted as the timing of the main inversion of this region with the creation of relief because of the shortening induced by the interplay between the African and Eurasian plates. Thermal modelling of samples co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
56
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(65 citation statements)
references
References 40 publications
6
56
0
3
Order By: Relevance
“…A significant amount of low-T geochronological studies has been performed in the High Atlas during the last years (Missenard et al 2008;Balestrieri et al 2009;Ghorbal 2009). Because of the lithological limitations imposed by the Apatite Fission Track and (U-Th)/He methods, practically all samples measured by the different authors originate from the MAM and, more specifically, from the Paleozoic basement and its stratigraphic cover of Triassic continental deposits.…”
Section: Upward Movements In the Mammentioning
confidence: 99%
“…A significant amount of low-T geochronological studies has been performed in the High Atlas during the last years (Missenard et al 2008;Balestrieri et al 2009;Ghorbal 2009). Because of the lithological limitations imposed by the Apatite Fission Track and (U-Th)/He methods, practically all samples measured by the different authors originate from the MAM and, more specifically, from the Paleozoic basement and its stratigraphic cover of Triassic continental deposits.…”
Section: Upward Movements In the Mammentioning
confidence: 99%
“…times (following Tesón et al, 2010;Aït Ouglif Formation age) witnessed the earliest recorded structural deformation and the development of the topography. This is shown by: (1) the setting of the various "nappes" across the High Atlas of Marrakech and the Central High Atlas (Laville et al, 1977; this study), (2) the influx of the unconformable detrital deposits of the Aït Ouglif formation (El Harfi et al, 2001), (3) the resuming of deformation, as suggested by a structural study of Tesón and Teixell (2008) and (4) the record of an important exhumation within the Marrakech High Atlas Balestrieri et al, 2009).…”
Section: Late Thick-skinned Deformationsmentioning
confidence: 85%
“…Following the studies of Missenard et al (2008) and Balestrieri et al (2009), based on lowtemperature thermochronology (LTT), we suggest that this Early(? )-Middle Miocene exhumation is linked to lithospheric thinning at that time (i.e.…”
Section: Early(?)-middle Miocene To Quaternary Deformations Eventsmentioning
confidence: 96%
See 1 more Smart Citation
“…Therefore, it seems less likely that the alluvial fans have significant contribution from other parts of the Red Sea coast by longshore currents. The denudation and erosion of the Eastern Desert have been investigated using apatite fission track dating (e.g., Omar and Steckler, 1995;Bojar et al, 2001;Abbate et al, 2002;Balestrieri et al, 2009). This dating indicates that the Arabian-Nubian Shield underwent uplift in two stages, an early uplift stage in the Oligocene (±35 Ma) and a later major uplift period in the Miocene (20)(21)(22)(23)(24)(25).…”
Section: Introductionmentioning
confidence: 99%